A Systematic Literature Review: PvK12 and PfK13 Gene Mutations as Markers of Resistance to Artemisin - Susiwati Susiwati; Chairil Anwar; Zen Hafy; Iche Andriyani Liberty (Indonesian Journal of Global Health Research, 2025)
P. falciparum and P. vivax are among the most dangerous types of plasmodium , as they cause morbidity and mortality. Long-term use of Anti-Malaria Drugs (OAM) causes resistance. The purpose of this study was to determine the mutation of the pvk12 and pfk13 genes as a marker of resistance to artemisinin . This study used a systematic review method that was compiled based on the Preferred Reporting Items for Systematic Reviews and Meta Analyzes (PRISMA). The article search used five databases, namely PubMed, Google Scholar, BMC, Portal Garuda and the National Library (Perpusnas) of Indonesia. The keywords and boolean operators used in the literature search were "artemisinin", "resistance", "mutation", "gen", "plasmodium falciparum", "kelch 12", "kelch 13", "PvK12" PfK13" The inclusion criteria for this study were articles published at least in 2018 (the last 5 years). The exclusion criteria were paid articles, textbooks , articles systematic literature review , articles that use languages other than English and Indonesian. The results of a systematic review use 688 articles and finished of 10 articles showed that 8 articles found that there were no mutations in the pvk12 and pfk13 genes as markers of resistance to artemisinin and 2 articles found that there were mutations in the pvk12 and pfk13 genes as markers of resistance to artemisinin.